Pengaruh transaksi non tunai terhadap velositas uang di Indonesia - Muhammad Lukmanulhakim; Syaipan Djambak; M. Komri Yusuf (Jurnal Ekonomi Pembangunan, 2016)
Current technological developments affecting the payment system. From Barter, Cash to non-cash payment. Nowadays, the most used non-cash payment instrument are Credit Card, Debit Card and E-Money. The use of this payment instrument make consumers easy to pay, thereby increasing the level of consumption. The objective of this study was to analyze the impact of the use of E-Money, Credit Cards and Debit Cards to the Velocity of Money in Indonesia. The data used is the number of transaction in 2010 to 2014. The analysis used was Johansen Co-integration Test to analyze the short-term effects and Error Correction Model to analyze the long term effects. The results of this study explains that the use of E-Money, Credit Cards and Debit Cards have long term effects, but there is no short-term effects on the Velocity of Money.